Effects on Physical Fitness and Stress between Dance Exergame and Home-Based Dance Exercise with Videos in Female Youths with Sedentary Behavior: An Assessor-Blinded Randomized Controlled Trial - Kaewmunee, Wanida; Sonthikul, Chatwalai; Thaworncheep, Naratorn; Jongkraijak, Kesornthip; Chotsampancharoen, Thidaporn; Pittapan, Pacharapon (ASEAN Journal of Rehabilitation Medicine, 2022)
Objectives: To compare the effects between dance exergame and home-based dance exercise with videos on physical fitness in female youths. Study design: an assessor-blind randomized controlled trial. Setting: Department of Physical Therapy, Faculty of Medicine, Prince of Songkla University, Songkhla, Thailand. Subjects: Thirty female youths with sedentary behavior. Methods: This study randomly divided the participants into the exergame group (n = 15), which received a dance exercise program with the Just Dance game, or the video group (n = 15), which received home-based dance exercise with videos. The exercise program for both groups started with 30 minutes, 5 times a week for two weeks then increased to 50 minutes, 3 times per week until the end of the program. Body mass index, percentage of body fat, muscle endurance, muscle strength, flexibility, agility and stress were measured at baseline, and then after 6 weeks of the exercise programs. Results: After the 6-week program, the exergame group showed improvement in all physical fitness outcomes, while the video group showed no difference in body mass index, percentage of body fat or agility. When comparing between the exergame and the video groups, differences were found in arm and upper body muscle endurance and back muscle strength when compared to the video groups (11 vs 1, p-value = 0.012 and 27 vs 20, p = 0.032, respectively): but not in stress (3 vs 2, p = 0.102). Conclusions: In female youths with sedentary behaviors, a 6-week program of exercise with dance exergame shows different effects on improving physical fitness when compared with home-based dance exercise with videos.